Espaces publics et mixité culturelle, pour un renouvellement du tourisme tunisien - Saloua Toumi; Roland Vidal (Projets de Paysage)
In the sixties, Bourguiba’s Tunisia had made the choice of developing a seaside tourism mainly aimed at the European middle classes. The economic efficiency of that choice, which resulted in the definition of coastal zones entirely devoted to tourism, has proved itself for several decades – up to the point that the economy of tourism has become one of the main sources of income for the country. So, it is not conceivable to radically go back on these orientations, all the more so as the facilities built on that purpose will be operational for years to come. Yet, one will have to take into account the probable evolution of the tourism demand. Indeed, the usual customers – who mainly seek the beach, the sun, and the sea; and only rarely the local culture – are also attached to the political stability of the country where they spend their holidays. And yet, they risk, rightly or wrongly, to perceive the Maghreb as a potentially unstable region in the years to come and, consecutively, to turn themselves towards other regions of the world which offer the same seaside assets and that appear to be more stable. On the other hand, it is probable that a new kind of customers will emerge – less interested in water recreation, and more interested in this Tunisian revolution that made the news worldwide. Will we be able to fulfil these expectations with the same hotel facilities conceived to keep the customers away from the Tunisian social life? We offer to analyse the story of the public space in Tunisia in order to better understand what has fundamentally changed since last January, and to plan how a redevelopment of the tourism zones could contribute to decompartmentalize these areas and turn them towards the “true country.”